Dynamic expression of Notch-dependent neurogenic markers in the chick embryonic nervous system - Leslie eRatié; Michelle eWare; Hélène eJagline; Véronique eDavid; Véronique eDavid; Valérie eDupé (Frontiers Media S.A., 2014)
The establishment of a functional nervous system requires a highly orchestrated process of neural proliferation and differentiation. The evolutionary conserved Notch signalling pathway is a key regulator of this process, regulating bHLH transcriptional repressors and proneural genes. However little is known about downstream Notch targets and subsequently genes required for neuronal specification.In this report, the expression pattern of Tagln3, Chga and Cntn2 was described in detail during early chick embryogenesis. Expression of these genes was largely restricted to the nervous system including the early axon scaffold populations, cranial ganglia and spinal motor neurons. Their temporal and spatial expression were compared with the neuronal markers Nhlh1, Stmn2 and HuC/D. We show that Tagln3 is an early marker for postmitotic neurons whereas Chga and Cntn2 are expressed in mature neurons. We demonstrate that inhibition of Notch signalling during spinal cord neurogenesis enhances expression of these markers. This data demonstrates that Tagln3, Chga and Cntn2 represent strong new candidates to contribute to the sequential progression of vertebrate neurogenesis.